2015
DOI: 10.1115/1.4029966
|View full text |Cite
|
Sign up to set email alerts
|

Film-Cooling Performance of a Turbine Vane Suction Side: The Showerhead Effect on Film-Cooling Hole Placement for Cylindrical and Fan-Shaped Holes

Abstract: In this paper, the transient IR-thermography method is used to investigate the effect of showerhead cooling on the film-cooling performance of the suction side of a turbine guide vane working under engine-representative conditions. The resulting adiabatic film effectiveness, heat transfer coefficient (HTC) augmentation, and net heat flux reduction (NHFR) due to insertion of rows of cooling holes at two different locations in the presence and absence of the showerhead cooling are presented. One row of cooling h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…5 In some research studies, it was shown that in the pulsed film cooling with a pulsating cooling air, the effectiveness has not been decreased or even it was enhanced in some cases. 6 The heat transfer mechanism in a single-phase flow has been extensively investigated, but there is little knowledge about the oscillation effects on heat transfer. In many industrial applications, pulsating flow occurs due to moving parts such as in pumps or turbines, or by vibrations and fluctuations.…”
Section: Introductionmentioning
confidence: 99%
“…5 In some research studies, it was shown that in the pulsed film cooling with a pulsating cooling air, the effectiveness has not been decreased or even it was enhanced in some cases. 6 The heat transfer mechanism in a single-phase flow has been extensively investigated, but there is little knowledge about the oscillation effects on heat transfer. In many industrial applications, pulsating flow occurs due to moving parts such as in pumps or turbines, or by vibrations and fluctuations.…”
Section: Introductionmentioning
confidence: 99%